UNDERSTANDING THE MOTIVATIONS AND OBSTACLES FACED BY FEMALE ENTREPRENEURS: A PHENOMENOLOGICAL STUDY OF GRADUATE MUMPRENEURS OF ISLAMABAD - Tariq, Jasim (PEOPLE: International Journal of Social Sciences, 2018)
Mumpreneurship remains an unexamined area in extant literature on female entrepreneurship of Pakistan. However, it is an emerging area of research in the developed world (Ekinsmyth, 2013). This study aims to understand the ‘essence’ of experiences of the Mumpreneurs i.e. female entrepreneurs in Pakistan having children. Thus, the focus of this phenomenological and qualitative study will be on their essence or shared entrepreneurial experiences. Therefore, the primary focus of this research project is to understand their motivations of starting own businesses, the problems and obstacles they may confront and how they are able to manage both their business enterprise and family roles that are expected of them. Thus, the findings of this research will help us to explore as how these mumpreneurs create balance between role of intensive mothering and business enterprise needs. Also, the study will enable us to understand as in what manner self-employment is more convenient to them to doing regular jobs especially under the background of social and religious conservatism prevailing in Pakistan (Roomi and Harrison, 2010). The author incorporated phenomenological methodology and semi-structured interviews to carry out this research on Mumpreneurs of Pakistan. The participants of this study were twelve female business owners with young children, from Islamabad categorized on a class basis. This study was an exploratory study on the understudied phenomenon of mumpreneurship in Pakistan. The validity of the study was ensured through rich and thick descriptions maintained by the author, disconfirming evidence and member checking. Moreover, the study was an attempt to understand essence of lived experience of female entrepreneurs with young children in starting and operating their businesses. The findings of this research can help us in understanding the underlying motivations and problems faced by mumpreneurs in Pakistan and their perceptions about the cultural environment that views them chiefly as homemakers.